Advances in environmental accounting & management : social and environmental accounting in Brazil - Belal, Ataur Rahman; Cooper, Stuart, 1970-; Freire, Fátima de Souza (Emerald Publishing Limited, 2017)
Vol 6 of Advances in Environmental Accounting & Management aims to advance knowledge of the governance and management of corporate environmental impacts and the accounting for these, including issues related to measurement, valuation, and disclosure. It is particularly relevant for accounting practitioners, investors and other stakeholders of the financial and social consequences of corporate environmental impacts.- Resumé vydavatel
Keywords: environmentální audit -- Brazílie; environmentální management -- Brazílie; environmental auditing -- Brasil; environmental management -- Brasil; kolektivní monografie; elektronické knihy; collective monographs; electronic books